Regresi Data Panel dan Aplikasinya dalam Kinerja Keuangan terhadap Pertumbuhan Laba Perusahaan Idx Lq45 Bursa Efek Indonesia - Nurul Madany; Ruliana Ruliana; Zulkifli Rais (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2022)
Regression is a statistical analysis that shows the relationship between one bound changer and one or more free changers. In the development of regression analysis, which can not only be observed at one time but can be observed in several time periods known as panel data regression. In conducting the regression analysis of panel data, there are three tests carried out to select a fixed model, namely the chow test, the Hausman test, and the pagan breucsh test. This study aims to see the influence of free variables, namely roa, roe, and npm on bound variables, namely company profit growth. The implementation of the method is carried out in the case of data on the financial performance of the LQ45 company and the growth of the company's profit LQ45. The result of the panel data regression modeling, namely the fixed effect model, is that financial performance has a significant effect on the company's profit growth whereas in the financial performance indicators the roa variable has a positive and significant influence and has a presentation that explains the free variables, namely roa, roe, and npm, on profit growth of the remaining 21% explained by other variables.